A study of adverse events of intra-hospital transportation of critically ill patients from the Emergency Department, Hospital Universiti Sains Malaysia - Hassan, Khairul Nizam (2006)
INTRODUCTION The transports of critically ill patients always involve some degree of risks to the patient and sometimes to the accompanying personnel. It has been stated that when a patient is transported from an ICU to a diagnostic area such as a radiology suite, they are not in a hospital, but only close to one. lntrahospital transport refers to transportation of patients within the hospital for a purpose of undergoing diagnostic or therapeutic procedures, or transfer to a specialised unit. The basic reason for moving a critically ill patient is the need for additional care, either technology and/or specialists not available at the patient's current location. The objectives of this study are: 1. To detennine the prevalence of adverse events during transfer of critically ill patients from emergency department to other specialised unit in HUSM. 2. To determine the prevalence for the requirement of therapeutic interventions during transport. 3. To determine the factors predicting the occurrences of adverse events and the requirement for major therapeutic intervention during the intrahospital transport. RESULTS A total of 257 transportations involving 247 critically-ill patients fulfilling the inclusion and exclusion criteria arrived to emergency deparbnent were included in this study over the period of twelve months. From this study, it was found out that: 1. There were no adverse events in 157 transports (61.5% ± 0.48). There was a significant in at least one variable in 100 transports (38.90/0 ± 0.48%). Of these 100 transports, 68 (26.5%) had derangement in only the physiologic variables, 15 (5.8%) had both a physiologic derangement and an equipment-related event, and 15 (5.9%) required at least one major intervention. At least one equipment-related adverse event occurred in 18 transports (7.0%). At least one major therapeutic intervention was performed in 15 transports (5.9%). 2. There was no arrest or death during transport. The requirement for a major procedure was 9.3% in mechanically ventilated patients versus 3.4% in non-ventilated patients. 3. Simple logistic regression analysis showed only pretransport Therapeutic Intervention Scoring System was significantly associated with the development of physiologic deterioration and the requirement for major intervention. The age and sex of the patient, and the number of escort personnel accompanying the transport did not affect the :frequency of adverse event. CONCLUSION From this study, majority of the critically ill patients transported from the Emergency Department developed serious physiologic adverse events during intrahospital transport. Some of the clinical predictors such as blood pressure, heart rate, respiratory rate and oxygen saturation by pulse oxymeter were shown to be a significant indicator in the development of adverse events during transport of critically ill patients. Severity of illness as shown by Therapeutic Intervention Scoring System (TISS) is significantly associated with the physiological occurrence of adverse event and major interventions. The team composition and equipment required on transport must be commensurate with the pretransport severity of illness.